APLIKASI PERSAMAAN ARRHENIUS DAN LINEAR UNTUK PENGUJIAN STABILITAS RETENSI IMPACT COMPOUND FLAVOR KWENI TERENKAPSULASI - Rini Hustiany (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Characteristic of high volatility in the flavor component is a problem at the time of application. The seven of flavor compounds used as a model, i.e ethyl butanoate, ethyl crotonate, a-pinene, myrcene, limonene, linalool, and a-terpineol encapsulated with stearic starch hydrolyzate and propionic starch hydrolyzate  by spray drying. The encapsulated flavor products stored in bottle at 30, 37,5, and 45 oC for 9 weeks. The  analysis is retention flavor with chromatography gas. Stability retention of flavor components were analyzed by Arrhenius and linear equation. The results showed the influence of temperature, the rate of decline in the stability of the encapsulated flavor component retention there is a difference between the matrix stearic starch hydrolyzate and propionic starch hydrolyzate. Components of flavor encapsulated in stearic starch hydrolyzate fastest down the stability of retention is linalool followed by a-terpineol, myrcene, limonene, and a-pinene. The flavor components encapsulated in propionic starch hydrolyzate  fastest down the stability of retention is  a-pinene followed by myrcene, linalool,  a-terpineol, and limonene.